2019
DOI: 10.1101/685081
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Alterations in brain network organization in adults with obesity as compared to healthy-weight individuals and seniors

Abstract: Life expectancy and obesity rates have drastically increased in recent years. An unhealthy weight is related to longlasting biological deregulations that might compromise the normal course of development and jeopardize the so-called "successful aging". The aim of the current study was to test whether an obesity status could mimic the functional organization of an otherwise healthy aged brain. Thus, the current study included adults with (N = 32, mean age 34.5 ± 6.49) and without obesity (N = 34, mean age 32.7 … Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2020
2020
2020
2020

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 52 publications
0
1
0
Order By: Relevance
“…Longitudinal evidence also points to an association between BMI changes and connectivity of reward and frontoparietal networks, both when studying healthy individuals, without any interventions (Park et al, 2019a) and in work that administered repetitive transcranial magnetic stimulation targeting the dorsolateral prefrontal cortex (Kim et al, 2019). Beyond local connectivity, a more recent study reported an increased modular segregation in individuals with obesity compared to individuals with healthy weight, suggesting a shift of brain organization towards more lattice like functional networks as BMI increases (Ottino-González et al, 2020). A more segregated network organization has previously been reported in several psychiatric and neurological diseases, including attention deficit hyperactivity disorder (Cao et al, 2014(Cao et al, , 2016(Cao et al, , 2013Liao et al, 2017;Wang et al, 2009), Alzheimer's disease (Bai et al, 2012;Dai and He, 2014;Liao et al, 2017;Zhao et al, 2012), as well as impulsivity (Davis et al, 2013).…”
Section: Discussionmentioning
confidence: 95%
“…Longitudinal evidence also points to an association between BMI changes and connectivity of reward and frontoparietal networks, both when studying healthy individuals, without any interventions (Park et al, 2019a) and in work that administered repetitive transcranial magnetic stimulation targeting the dorsolateral prefrontal cortex (Kim et al, 2019). Beyond local connectivity, a more recent study reported an increased modular segregation in individuals with obesity compared to individuals with healthy weight, suggesting a shift of brain organization towards more lattice like functional networks as BMI increases (Ottino-González et al, 2020). A more segregated network organization has previously been reported in several psychiatric and neurological diseases, including attention deficit hyperactivity disorder (Cao et al, 2014(Cao et al, , 2016(Cao et al, , 2013Liao et al, 2017;Wang et al, 2009), Alzheimer's disease (Bai et al, 2012;Dai and He, 2014;Liao et al, 2017;Zhao et al, 2012), as well as impulsivity (Davis et al, 2013).…”
Section: Discussionmentioning
confidence: 95%